The Need for Management of Entrepreneurship Education among Undergraduate Students: A Case of Nasarawa State University, Keffi–Nigeria - Yohanna, Agana Timothy (International Journal of Current Innovations in Advanced Research, 2023)
Management of entrepreneurship education has become a thing of concern in Nigeria. This paper examines management of entrepreneurship education in terms of its relevance to functionality and solving problems of students and graduates alienation after several years of schooling. Descriptive survey research design was adopted in this study. The target population for the investigation consists of 567 respondents within Nasarawa state university, Keffi who registered entrepreneur. Simple random sampling strategy was adopted to select 373 students from the study area. The analysis of the results base on table B which shows the regression and residual. The table carried out the sum of squares of 6.760, 366.882 with the degree of 9, mean square of 0.52 and 1.013 with the significant of 0.741.Since the grade point average is 2.66 that is to say there is positive relationship between managing of entrepreneurship among undergraduate students in Nasarawa State University, Keffi. The finding showed that the mean of grade point average of students was 2.66. Also according to the coefficient variation, the highest of managing entrepreneurial among students were perseverance, self-confidence, and need for achievement. The study recommended that government should establish a Quality Assurance Commission for ECCDE/Basic and Post Basic Education sub sectors as this will serve as good foundational level for higher education.